ILLUSTRATED HUMAN ANATOMY : THE AUTHORITATIVE VISUAL GUIDE TO THE HUMAN BODY - Vayttaden, Sharat; Gustafson, Dana, Dr. (Buffalo, New York : Firefly Books Ltd., 2021)
Packed with astonishing facts and superb quality 3-D illustrations, Illustrated Human Anatomy is a state-of-the art guide to the human body that is destined to become the definitive illustrated human anatomy reference. Accessible text and detailed annotations give the names of organs and structures throughout the skeletal, muscular, lymphatic, cardiovascular, nervous, and reproductive systems, with focus features reviewing disorders of each system. Illustrated Human Anatomy features the same precise 3-D illustrations used by medical schools and hospitals -- the accuracy is without par. Spreads feature a variety of body parts, such as muscle, bone, soft tissue and vascular, with explanatory text by Dr. Milnes, as well as sidebars and boxes. All images are fully annotated and may be shown in a variety of presentations: cross-sections; views (front, top, side); projections; and overlays. Focus facts appear in balloons and other call-outs, and there are feature spreads throughout, such as one on fetal development. The illustrations are from SciePro, the world's pre-eminent medical science graphics studio of its kind. It has compiled a library of 50,000 scientific illustrations, animations and 3-D digital animated models of the human body, the most detailed and medically accurate available. To date they are have been used in more than 700 projects by pharmaceutical, medical, and scientific clients around the globe, such as Stanford University and Ohio State University, Swiss Surgery, Proctor and Gamble, NextBio, St. Jude Medical, Pfizer and Endostim.
Includes index.
Keywords: Human anatomy -- Atlases